(untitled) (UNED Research Journal, 2020)
Introduction: Tropical riparian ecosystems are poorly known and integrate abiotic and biotic factors in the landscape, defining ecological processes along the river. Objective: To measure physical and biological indicators along a tropical river. Methods: Work was carried out in four Representative Zones of the Torres river during 2014 and 2015. At each site, the following were analyzed: a) soil loss; b) diversity of plants and vegetation cover; c) richness of birds; d) physicochemical and bacteriological parameters of the water. We worked with the Urban Ecosystem Quality Index of the Torres River (ICEURT) and the Water Quality Index (ICA-NSF). Results: A total of 365 plant species were identified, with the most diverse zone having 320 species. The coverage percentage ranged from 60% to 81% in the lower-middle part. Birds included 90 species in 28 families, 66% were residents; the highest bird richness in a zone was 55 species. The habitat quality was intermediate in all zones, with the middle part of the river having problems in bird and plant diversity; while, the lower part as low in plant richness. Water quality was medium to poor in all zones. All variables were zone-dependent (X2=53,813; p<0,05). Conclusions: Ecosystem quality varied along the river, with generally medium to low values in biota and low values in water quality.